Direct current electrical stimulation chamber for treating cells in vitro. (February 2016) - Mobini, Sahba; Leppik, Liudmila; Barker, John H.
Electrical stimulation has been shown to promote healing and regeneration in skin, bone, muscle, and nerve tissues in clinical studies. Recently, studies applying electrical stimulation to influence cell behavior associated with proliferation, differentiation, and migration have provided a better understanding of the underlying mechanisms of electrical stimulation—based clinical treatments and improved tissue-engineered products through electro-bioreactor technologies. Here, we present a novel device for delivering direct current (DC) electrical stimulation (ES) to cultivated cells in vitro. Our simplified electro-bioreactor is customized for applying DC electrical current simultaneously in six individual tissue culture wells. The design overcomes previous experimental replicate limitations, thus reducing experimental time and cost.